ANALISIS STRATEGI KOMUNIKASI DALAM MENINGKATKAN CITRA EKOWISATA RIAM KANAN DI KALIMANTAN SELATAN - Siswanto Siswanto; Muhammad Muthahhari Ramadhani (Metacommunication: Journal of Communication Studies, 2021)
The potency of the water tourism object in Riam Kanan reservoir is not well known by both domestic and foreign tourists because the communication strategy program has not been maximized by the local government. An important factor in raising the image of ecotourism is the communication strategy policy in order to promote it to a wide audience. Communication strategy is a combination of communication planning and communication management to achieve a goal. The method used in this research is a qualitative approach with the type of case study research. Data collection techniques that researchers use are field research and literature study. The results showed that the communication strategy carried out by the Department of Tourism and Culture of Banjar Regency in enhancing the ecotourism image of the Riam Kanan reservoir has followed the procedure as in communication theories, namely establishing communicators. setting targets, compiling communication messages and, selecting media and channels communication. The media used include outdoor media, small format media, print media, electronic media, internet and social media as well as other public communication channels.